Oswald Spengler als europäisches Phänomen : der Transfer der Kultur- und Geschichtsmorphologie im Europa der Zwischenkriegszeit 1919 - 1939 - Gasimov, Zaur T. 1981-; Lemke Duque, Carl Antonius; Spengler, Oswald 1880-1936 BeteiligteR (Veröffentlichungen des Instituts für Europäische Geschichte Mainz Beiheft Abteilung für Universalgeschichte, 2013)
"There was hardly another German author from the first half of the 20th century who was quoted, reviewed and criticized so often in the time immediately after World War I as the philosopher of culture and history Oswald Spengler (1880-1936). The contributions in this volume represent the first systematic look at the phenomenon of the many ways in which Spengler's philosophy was 'transferred' in Europe between the two world wars. They investigate the deep impact of the various levels of his literary reception in Western, Eastern and Southern Europe"--Publisher's website